Impact of sustained viral response postcurative therapy of hepatitis C‐related hepatocellular carcinoma: a systematic review and meta‐analysis. Issue 5 (19th December 2016) - Manthravadi, Sashidhar; Paleti, Swathi; Pandya, Prashant
Abstract : Antiviral therapy with interferon based therapies (IBT) has shown potential in improving survival in patients who have undergone resection or locoregional therapy for hepatitis C‐associated hepatocellular carcinoma (HCV‐HCC). However, this benefit has not been definitively ascribed to sustained viral response (SVR). Since IBT has been replaced with new directly acting agents (DAA), which are more efficacious in the treatment of HCV, we sought to better determine the prognostic impact of SVR in HCV‐HCC. A systematic search of MEDLINE and EMBASE from inception through October 2015 was performed to identify studies that described the impact of presence of SVR in patients who underwent curative treatment of HCV‐HCC. Summary hazard ratio (HR) with 95% confidence intervals (CI) was estimated for recurrence‐free survival (RFS) and overall survival (OS) utilizing a random‐effects model. After reviewing 858 abstracts, ten studies which included a total of 1, 794 patients were selected and data was extracted. Of these ten studies, the impact of SVR on RFS and OS was reported in eight and seven studies respectively. In a meta‐analysis which included 1, 519 patients, SVR was associated with improved OS (HR 0.18; 95% CI 0.11–0.29, I 2 = 2%). We also found that SVR was associated with better RFS in a meta‐analysis (1, 241 patients; HR 0.50; 95% CI 0.40–0.63, I 2 = 0). In conclusion, SVR is associated with improved OS and RFS in patients with HCV who have undergone resection or locoregional therapy for HCC. Newer DAA therapies which offer increased tolerability and viral eradication should be considered as adjunctive therapy. Abstract : What's new? Interferon‐based therapy (IBT) has been shown to be efficacious in improving outcomes in patients with hepatitis C virus‐associated hepatocellular carcinoma (HCV‐HCC). While viral eradication has been hypothesized to be the major factor underlying interferon efficacy, the impact of sustained viral response (SVR) on survival and local recurrence in patients treated with IBT remains ill‐defined. In this meta‐analysis of observational studies, the authors demonstrate that SVR is a prognostic biomarker in patients with HCV‐HCC who have undergone resection or locoregional therapies. Given the dramatic improvement in SVR with new direct‐acting agents, studies evaluating their use as adjuvant therapy are needed.